Evaluasi User Engagement dan User Experience pada Aplikasi Satu Sehat - Fandi Halim; Riche Suwandy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Various efforts to prevent and trace the wider spread of the Covid-19 Virus have been carried out by the government. One of them is done with through technology by providing the application namely SatuSehat application which has variety of features aimed on helping the society. However, along with the imminent evolution of this application into SatuSehat application, these various features that exist, are still rarely known by the public. In addition, from previous studies, there are user experience evaluation has been carried out which shows that low evaluation results. Even though this application has been widely downloaded by the public. This study is aimed at re-measuring the user experience of SatuSehat application and is accompanied by user engagement evaluation to SatuSehat application and its relationship with the user experience. User experience evaluation will utilize the UEQ-S method while the user engagement evaluation will utilize the UEQ-SF method. The results showed that SatuSehat application has a positive overall user experience evaluation result which is supported by quite good user engagement evaluation results. The results of the study even show that there is a strong correlation between user engagement and user experience from the SatuSehat application.